1983
DOI: 10.1016/s0022-5347(17)52089-3
|View full text |Cite
|
Sign up to set email alerts
|

Character of Urinary Tract Infections and Pyelonephritic Renal Scarring After Antireflux Surgery

Abstract: We followed 40 girls who had undergone antireflux surgery (the Politano-Leadbetter technique) at the mean age of 5.2 years until they reached a mean age of 9.5 years. Each girl was matched with a control. The pairs were matched for age at the onset of urinary tract infections and time of operation or selection, number as well as grade (1 to 3) of severity of the preoperative episodes and grade (II to IV) of reflux. Followup time for each member of the pair was identical. Postoperatively, the incidence of pyelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 11 publications
1
8
0
4
Order By: Relevance
“…Other uncontrolled studies give, irrespective of operation or medical management, the same results for development of new scars (21)(22)(23). Interestingly, the same rate of new scars among operated girls and their controls was also reported by Elo et al in a retrospective study, in which no prophylaxis was given to the conservatively managed group (24). However, no results are available for an unselected population of children with reflux on development of new renal scarring, which compare children on prophylaxis with children managed without prophylaxis.…”
Section: Protection Against New Renal Scarring and Progressive Parencsupporting
confidence: 64%
“…Other uncontrolled studies give, irrespective of operation or medical management, the same results for development of new scars (21)(22)(23). Interestingly, the same rate of new scars among operated girls and their controls was also reported by Elo et al in a retrospective study, in which no prophylaxis was given to the conservatively managed group (24). However, no results are available for an unselected population of children with reflux on development of new renal scarring, which compare children on prophylaxis with children managed without prophylaxis.…”
Section: Protection Against New Renal Scarring and Progressive Parencsupporting
confidence: 64%
“…Pyelonephritic symptoms, including febrile utis, tended to be more common in the medically treated groups compared with the surgical groups. [32][33][34] in general, new scars occurred earlier in children treated surgically compared with those in the medical treatment groups, but, as noted, no signifi cant difference occurred overall with longer follow-up in terms of new renal scars in those treated with antibiotics compared to those undergoing surgery. 5,35 these observations suggested that a potential benefit of anti-reflux surgery might be a reduction in pyelonephritis in some patients; however, other researchers suggested that, once renal scarring occurs, the disease tends to run its course and operative treatment has little benefit.…”
Section: Clinical Managementmentioning
confidence: 78%
“…Recent prospective studies have shown that parenchy mal damage can be prevented by long-term chemopro phylaxis or a reflux operation [1][2][3]. The outcome of conservative therapy, however, depends on strict chemo prophylaxis until the disappearance of VUR is con firmed radiologically.…”
Section: Introductionmentioning
confidence: 99%